Synthesis Of Selenium Nanoparticles - Farah S. Daabool; Emad Khalifa; Ali Hadi (Genius Journals, 2021)
Selenium is a trace micronutrient that is necessary for human, animal, and microbial health. Many academics have recently become interested in selenium nanoparticles (SeNPs) due to its biocompatibility, bioavailability, and low toxicity. keywords: selenium , nanoparticles ,XRD,SEM. As a result of their increased bioactivity, selenium nanoparticles are widely used in a variety of biological applications. Physical, chemical, and biological approaches can all be used to make selenium nanoparticles. The organically generated SeNPs, on the other hand, are more compatible with human organs and tissues. Many studies have looked at the impact of size, shape, and the technology used to synthesize them on their applicability in biological systems. This article examines the numerous synthesis processes used to make them, as well as their biological applications, including as the treatment of fungal, bacterial, and parasite infections, cancer, and diabetes . They can also be used as chemopreventive, anti-inflammatory, and antioxidant agents.el.
Keywords: Nanoparticles; selenium; XRD